Cultural tightness-looseness: Its nature and missiological applications. Issue 4 (October 2019) - Dunaetz, David R.
The focus of much missionary work concerns sharing the gospel with others so that they may put their faith in Jesus Christ. However, members of some cultures are much more resistant to this than are members of other cultures. The concept of cultural tightness-looseness helps explain why some cultures are more closed to the gospel than are others. Tight cultures, in contrast to loose cultures, have strong social norms, violations of which are met with intense sanctions. Numerous recent studies reveal the antecedents, consequences, and the geographical distribution of cultural tightness-looseness. There are important missiological implications at the societal level, the individual level, and the organizational level when missionaries work in host cultures which are tighter than their home cultures. Understanding these implications can help the missionary better love and respond to the needs of members of their host culture.